Low pre-vaccination SARS-CoV-2 seroprevalence in Finnish health care workers: a prospective cohort study. Issue 6 (3rd June 2022) - Tähtinen, Paula A.; Ivaska, Lauri; Jalkanen, Pinja; Kakkola, Laura; Kainulainen, Leena; Hytönen, Jukka; Vuorinen, Tytti; Waris, Matti; Peltola, Ville; Oksi, Jarmo; Julkunen, Ilkka; Lempainen, Johanna
Abstract: Background: Health care workers are at risk of acquiring SARS-CoV-2 infection. Our aim was to study the prevalence of SARS-CoV-2 nucleoprotein and spike protein specific antibodies in health care workers with occupational exposure to COVID-19 in Turku, Finland, from May to December 2020. Methods: Health care workers of Turku University Hospital units caring for COVID-19 patients or handling clinical SARS-CoV-2 samples were invited to participate in the study. The presence of SARS-CoV-2 nucleoprotein and spike protein specific IgG antibodies were analysed with in-house enzyme immunoassay. Results: At study enrolment, only one of the 222 (0.5%) study participants was seropositive for SARS-CoV-2 protein specific antibodies. Two additional study participants (2/222, 0.9%) seroconverted during the follow-up. All these participants were diagnosed with a RT-PCR-positive COVID-19 infection before turning seropositive. Conclusion: In our study population, the prevalence of SARS-CoV-2 seropositivity remained low. The absence of seropositive cases without previous RT-PCR confirmed infections demonstrate good access to diagnostics. In addition to high vaccine coverage, high standards of infection prevention practices and use of standard personal protective equipment seem sufficient in preventing occupational SARS-CoV-2 infection in a setting with low number of circulating virus. However, it remains unclear whether similar protective practices would also be effective against more transmissible SARS-CoV-2 variants.